2014
DOI: 10.1007/s00520-014-2332-y
|View full text |Cite
|
Sign up to set email alerts
|

Loss of muscle mass in the end of life in patients with advanced cancer

Abstract: Muscle loss in advanced cancer is related to age, sex, tumor type, and inflammation. The mechanism(s) behind the apparent sexual dimorphism warrants further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
59
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(65 citation statements)
references
References 42 publications
2
59
0
1
Order By: Relevance
“…Wallengren and co-workers found a higher loss of muscle mass in men with advanced tumor stages than in women. Furthermore, this loss was associated with age, tumor type and concomitant inflammatory conditions [19]. In addition, a decrease of phase angle was seen in our patients that reached significance in male patients.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Wallengren and co-workers found a higher loss of muscle mass in men with advanced tumor stages than in women. Furthermore, this loss was associated with age, tumor type and concomitant inflammatory conditions [19]. In addition, a decrease of phase angle was seen in our patients that reached significance in male patients.…”
Section: Discussionmentioning
confidence: 54%
“…The patients often suffer from absence of appetite, abdominal pain, diarrhea, anorexia, back pain, fatigue, jaundice, diabetes, maldigestion and systemic inflammation [13,18]. The same holds true for biliary tract cancer [19]. Furthermore, there are changes in metabolism by an increased protein catabolism and energy expenditure [20].…”
Section: Introductionmentioning
confidence: 99%
“…A previous study also described disagreement between different muscle measures in patients with cancer,25 whereby low muscle mass according to MUAMC was prevalent in 15% of patients and according to DEXA in 67% of the same patients. Another study showed that prevalence of low muscle mass ranged between 52 and 86% in elderly patients, dependent of type of muscle measurement and chosen cut‐off value 26.…”
Section: Discussionmentioning
confidence: 94%
“…This age-group, already at higher risk to be deficient in muscle due to age-related decline, is then at high risk to lose additional muscle due as their cancer progresses and they receive anti-cancer therapy. Advanced cancer patients lose up to 1.5 kg of lean mass per year (84). Studies have also demonstrated that muscle mass directly correlates with survival in cancer patients (85,86).…”
Section: Potential Clinical Uses Of Sarmsmentioning
confidence: 99%